Mecanismos associados aos padrões de distribuição de peixes não nativos em reservatórios neotropicais. - Ferreira, Eveline de Almeida (2012)
Freshwater ecosystems are among the most affected by human activity, and the factors related to these changes are hydrological alterations and biological invasions. In this context, we investigated the mechanisms related to the patterns of non-native fish distribution in 76 reservoirs located in the Paraná River basin. Specifically, the relative importance of biotic acceptance, biotic resistance, human activity hypotheses, connectivity and distance from donor source of propagules, and life history characteristics to the patterns of non-native richness and distribution were tested. The information on the distribution of fish species were obtained from compilations. Likewise, the explanatory variables were obtained from literature and electronic databases. The explanatory variables were used to quantify the environmental variation of reservoirs in the local and regional scales and were selected to represent the initial hypotheses of the study. A hierarchical partitioning model was used to quantify the independent effects of explanatory variables on the variation of non-native species richness. To assess the types of relationships between explanatory variables and non-native species richness were applied a generalized linear model. To evaluate the relationship between life history characteristics of non-native species and their spatial distributions, we first calculated a principal coordinate analysis. Then, the principal coordinate scores were correlated with the non-native species relative frequency considering 64 reservoirs. The results demonstrated that the non-native fish richness in the Paraná Basin reservoirs was mainly associated with native species richness, connectivity and distance from donor propagules, and reservoirs physical and geographical characteristics. Additionally, species with opportunistic strategy were more common in the reservoirs analyzed. These results suggest that mechanisms of biotic acceptance, dispersal limitation and species-specific adaptations may be important determinants of the establishment of non-native species in reservoirs of the Paraná Basin.